A pragmatic randomised controlled trial (RCT) and realist evaluation of the interdisciplinary home-bAsed Reablement program (I-HARP) for improving functional independence of community dwelling older people with dementia: an effectiveness-implementation hybrid design - Yun-Hee Jeon; Judy M. Simpson; Lee-Fay Low; Robert Woods; Richard Norman; Loren Mowszowski; Lindy Clemson; Sharon L. Naismith; Henry Brodaty; Sarah Hilmer; Amanda Miller Amberber; Laura N. Gitlin; et al. (BMC Geriatrics, 2019)
Abstract Background A major gap exists internationally in providing support to maintain functional and social independence of older people with dementia living at home. This project evaluates a model of care that integrates evidence-based strategies into a person-centred interdisciplinary rehabilitation package: Interdisciplinary Home-bAsed Reablement Program (I-HARP). Two central aims are: 1) to determine the effectiveness of I-HARP on functional independence, mobility, quality of life and depression among people with dementia, their home environmental safety, carer burden and quality of life, and I-HARP cost-effectiveness; and 2) to evaluate the processes, outcomes and influencing factors of the I-HARP implementation. Methods I-HARP is a 4-month model of care, integrated in community aged care services and hospital-based community geriatric services, and consists of: 1) 8–12 home visits, tailored to the individual client’s needs, by an occupational therapist, registered nurse, and other allied health staff; 2) minor home modifications/assistive devices to the value of <A$1000 per participant; and 3) three individual carer support sessions. The overarching design is a mixed-methods action research approach, consisting of a multi-centre pragmatic parallel-arm randomised controlled trial (RCT) and realist evaluation, conducted in two phases. Participants include 176 dyads (person aged > 60 years with mild to moderate dementia and his/her carer). During Phase I, I-HARP advisory group is established and training of I-HARP interventionists is completed, and the effectiveness of I-HARP is examined using a pragmatic RCT. Phase II, conducted concurrently with Phase I, focuses on the process evaluation of the I-HARP implementation using a realist approach. Semi-structured interviews with participants and focus groups with I-HARP interventionists and participating site managers will provide insights into the contexts, mechanisms and outcomes of I-HARP. Discussion I-HARP is being evaluated within the real-world systems of hospital-based and community-based aged care services in Australia. Future directions and strategies for reablement approaches to care for community dwelling people living with dementia, will be developed. The study will provide evidence to inform key stakeholders in their decision making and the use/delivery of the program, as well as influence future systems-thinking and changes for dementia care. Trial registration Australian New Zealand Clinical Trial Registry ACTR N12618000600246 (approved 18/04/2018).